Understanding Differentiated Learning Among Geography Teachers: Impact of Curriculum Training in Indonesian High Schools - Sugiyanto Sugiyanto; Rita Noviani; Chatarina Muryani; Singgih Prihadi; Imasti Dhani Pratiwi (STAI Hubbulwathan Duri, 2025)
Differentiated instruction is a key component of the Merdeka Belajar Curriculum (Freedom to Learn), aiming to meet diverse student needs in the classroom. However, the extent to which geography teachers understand and implement this approach remains underexplored in the Indonesian context. This quantitative descriptive study used a structured online questionnaire based on Tomlinson Imbeau’s four differentiation dimensions: content, process, product, and learning environment. A total of 59 geography teachers from senior high schools across Indonesia participated, all of whom met eligibility criteria including prior curriculum training. Data were analyzed using descriptive statistics and hierarchical regression via SPSS. Findings show that 66.1% of teachers demonstrated a high level of understanding, and 33.9% a moderate level; none were in the low category. Regression analysis revealed that participation in Merdeka Curriculum training significantly predicted understanding of differentiated learning (p 0.01), while being a geography teacher alone had no significant effect. Although conceptual understanding is high, implementation remains limited due to a lack of practical training and systemic support. The findings highlight the critical role of subject-specific, practice-based professional development. Geography, as a context-rich subject, offers strong potential for differentiation, yet requires targeted strategies and ongoing support to bridge the gap between theory and classroom practice.